iconic structures and the image of the city - Lidin, Konstantin (project baikal, 2018)
To see the city as a whole, it is necessary either to rise to a height of several kilometers above it or to live in it for many years; either to size it up at a glance, regardless of details, or to gradually assemble a number of concrete details and impressions into an overall picture. But the image of the city is more often composed of several most outstanding landmarks. The image of the city is like an identikit picture: a haircut, a forehead, eyes, a nose, a chin… The kit of elements that make the image of the city recognizable used to be published as a kit of postcards in the Soviet times. It was good from the point of view of the laws of perception. In this section, we have included a few examples of how single landmarks express and contain the image of the whole city, and how they become a symbol and generalization of this image.